Systematic comparison of plasma EBV DNA, anti‐EBV antibodies and miRNA levels for early detection and prognosis of nasopharyngeal carcinoma - Tan, Lu Ping; Tan, Geok Wee; Sivanesan, Vijaya Mohan; Goh, Siang Ling; Ng, Xun Jin; Lim, Chun Shen; Kim, Wee Ric; Mohidin, Taznim Begam Mohd; Mohd Dali, Nor Soleha; Ong, Siew Hoon; Wong, Chun Ying; Sawali, Halimuddin; et al. (John Wiley & Sons, 2020)
Nasopharyngeal carcinoma (NPC) is originated from the epithelial cells of nasopharynx, Epstein–Barr virus (EBV)-associated and has the highest incidence and mortality rates in Southeast Asia. Late presentation is a common issue and early detection could be the key to reduce the disease burden. Sensitivity of plasma EBV DNA, an established NPC biomarker, for Stage I NPC is controversial. Most newly reported NPC biomarkers have neither been externally validated nor compared to the established ones. This causes difficulty in planning for cost-effective early detection strategies. Our study systematically evaluated six established and four new biomarkers in NPC cases, population controls and hospital controls. We showed that BamHI-W 76 bp remains the most sensitive plasma biomarker, with 96.7% (29/30), 96.7% (58/60) and 97.4% (226/232) sensitivity to detect Stage I, early stage and all NPC, respectively. Its specificity was 94.2% (113/120) against population controls and 90.4% (113/125) against hospital controls. Diagnostic accuracy of BamHI-W 121 bp and ebv-miR-BART7-3p were validated. Hsa-miR-29a-3p and hsa-miR-103a-3p were not, possibly due to lower number of advanced stage NPC cases included in this subset. Decision tree modeling suggested that combination of BamHI-W 76 bp and VCA IgA or EA IgG may increase the specificity or sensitivity to detect NPC. EBNA1 99 bp could identify NPC patients with poor prognosis in early and advanced stage NPC. Our findings provided evidence for improvement in NPC screening strategies, covering considerations of opportunistic screening, combining biomarkers to increase sensitivity or specificity and testing biomarkers from single sampled specimen to avoid logistic problems of resampling. © 2019 The Authors. International Journal of Cancer published by John Wiley & Sons Ltd on behalf of UICC